IMPLIKASI PERANG SIBER ANTARA ISRAEL, AMERIKA SERIKAT DAN IRAN MELALUI OLIMPIC GAME OPERATION TERHADAP FASILITAS PROGRAM NUKLIR IRAN PADA PERIODE PEMERINTAHAN MAHMOUD AHMADINEJAD: PERANG SIBER STUXNET 2010 - Ayunita Harianja; Adi Rio Arianto; M. Chairil Akbar Setia (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Iran's nuclear program is the most collaborative in the Middle East region. International criticism regarding the development of the program did not make Ahmadinejad to stop the nuclear program in Iran. The United States decided to take action regarding Iran's nuclear program by cooperating with Israel to carry out attacks on nuclear facilities Israel is located in the Natan region. This attack is known as the Olympic Game Operation with the code